Neural correlates of overvaluation and the effort to save possessions in a novel decision task: An exploratory fMRI study - Liu, Tingting; Vickers, Brian D.; Seidler, Rachael D.; Preston, Stephanie D. (Frontiers in Psychology, 2023)
Introduction People exhibit a strong attachment to possessions, observed in behavioral economics through loss aversion using new items in the Endowment or IKEA effects and in clinical psychology through pathological trouble discarding domestic items in Hoarding Disorder. These fields rarely intersect, but both document a reticence to relinquish a possessed item, even at a cost, which is associated with feelings of loss but can include enhanced positive states as well. Methods To demonstrate the shared properties of these loss-related ownership effects, we developed the Pretzel Decorating Task (PDT), which concurrently measures overvaluation of one’s own over others’ items and feelings of loss associated with losing a possession, alongside enhanced positive appraisals of one’s items and an effort to save them. The PDT was piloted with 31 participants who decorated pretzels and responded to their own or others’ items during functional neuroimaging (fMRI). Participants observed one item per trial (self or other) and could work to save it (high or low probability loss) before learning the fate of the item (trashed or saved). Finally, participants rated items and completed hoarding tendency scales. Results The hypotheses were supported, as even non-clinical participants overvalued, viewed as nicer, feared losing, and worked harder to save their items over others’—a response that correlated with hoarding tendencies and motor-motivational brain activation. Our region of interest in the nucleus accumbens (NAcc) was engaged when viewing one’s own items to the extent that people worked harder to save them and was more active when their items were saved when they felt emotionally attached to possessions in real life. When their items were trashed, NAcc activity negatively correlated with trouble discarding and emotional attachments to possessions. Right anterior insula was more active when working to save one’s own over others’ items. Extensive motor-motivational areas were engaged when working to save one’s own over others’ items, including cerebellum, primary motor and somatosensory regions, and retrosplenial/parahippocampal regions—even after controlling for tapping. Discussion Our attachments to items are emotional, continuous across typical and pathological populations, and drive us to save possessions that we value.